Iddah of Women Who Had Abortus in The Book of Mughni al-Muhtaj and Mukhtashar Khalil in Perspective of Maqashid Shari’ah - Wika Wulandari (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
Iddah is a period of waiting for a woman not to carry out a marriage after the death or divorce of her husband until the time limit determined by syara‘. As for the iddah period for a woman who is pregnant until she gives birth. However, the problem that arises in this life is what if the woman has an abortion. In this matter, there is a difference of opinion in the books of Mughni al-Muhtaj and Mukhtashar Khalil about the end of the iddah period of a woman who has an abortion. This research aims to find out how the opinions of the two books about iddah women who experience abortion and what causes differences of opinion, and which opinion is chosen. This research is a type of library research, which is descriptive with qualitative analysis, and the primary data source used is the book of Mughni al-Muhtaj and Mukhtashar Khalil. This study indicates that the difference in opinion is due to differences in the book’s writers in interpreting the word al-haml and the rules of ushul fiqih used. Moreover, from the two opinions, Muhammad Khatib asy-Syarbaini in the book Mughni al-Muhtaj which was chosen because it followed the wisdom of determining iddah.